1996
DOI: 10.1159/000111429
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Astrocytes in Glucose Delivery to Neurons?

Abstract: The present paper examines the possible role of astrocytes in the delivery of glycogen-derived glucose for neuronal metabolism. Such a process would require astrocytic expression of glucose-6-phosphatase. The degree and significance of brain expression of glucose-6-phosphatase (EC 3.1.3.9) has been a subject of controversy. Published immunohistochemical data are consistent with expression of glucose-6-phosphatase by astrocytes, both in vivo and in vitro. In this paper additional confirmation of the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…Our findings regarding the enhanced susceptibility of astrocytes to UCB toxicity may be of great relevance because glial cells seem to play a key role in the maintenance of brain function (23). In addition, interdependence of astrocytes and neurons has been demonstrated in studies reporting that astrocytes deliver glutamine and glucose to neurons (24,49), and protect neuronal cells from toxic agents (25,50,51).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Our findings regarding the enhanced susceptibility of astrocytes to UCB toxicity may be of great relevance because glial cells seem to play a key role in the maintenance of brain function (23). In addition, interdependence of astrocytes and neurons has been demonstrated in studies reporting that astrocytes deliver glutamine and glucose to neurons (24,49), and protect neuronal cells from toxic agents (25,50,51).…”
mentioning
confidence: 61%
“…Although neurons have been suggested as more susceptible than astrocytes (13), more recent reports describe compromised astrocyte function following UCB interaction (19 -22). Evidence is also arising on the influence of astrocytes in neuronal function, metabolism, and survival (23)(24)(25)(26). The role of astrocytes on UCB toxicity is further reinforced by electron microscopic and autoradiographic studies on experimental kernicterus, indicating that these cells represent the main transporters of UCB from blood to neurons and are also involved in the release of waste products from UCB damaged neurons (27,28).…”
mentioning
confidence: 99%
“…A trafficking pathway for delivery of nutrients and metabolites between astrocytes and neurons is supported by previous studies. Astrocytes have been implicated in the delivery of glucose and lactate to neurons (19) and are known to play an important role in the uptake and recycling of neuronally released glutamate (20). In this respect it is of interest that glutamine synthetase in human cerebral cortical astrocytes is localized in a manner that closely resembles the perisynaptic astrocytic localization of NPC1 in this study (16).…”
Section: Discussionmentioning
confidence: 87%
“…They scattered throughout the tectum and substantia nigra within ventrolateral tegmentum. In addition to contributing to the metabolism and neurotransmission (Forsyth et al 1996), astrocytes may be involved in inducing specific neurochemical phenotypes. Investigation revealed that induction of a ventral mesencephalic dopaminergic phenotype could be fulfilled by diffusible factors derived from local subtype of astrocytes (Wagner et al 1999).…”
Section: The Corresponding Roles Played By Astrocytes In Mesencephalonmentioning
confidence: 99%